2008
DOI: 10.1097/hjh.0b013e328304dbff
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody against AT1 receptor from preeclamptic patients induces vasoconstriction through angiotensin receptor activation

Abstract: Preeclampsia is a serious pathologic complication during pregnancy, and its pathogenesis remains poorly understood. Recent studies have demonstrated that autoantibodies against angiotensin II type 1A receptor (AT1-AA) are present in women with preeclampsia. However, their role in the development of hypertension in preeclamptic patients has never been previously investigated. The present study was designed to determine whether AT1-AA isolated from the sera of preeclamptic patients causes vascular constriction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 23 publications
(24 reference statements)
3
42
0
Order By: Relevance
“…It has been demonstrated that AT1-AAs increased the expression of tissue factor [24] , induced Ca 2+ release [25] and activated NADPH oxidase [10] in VSMCs [9] . Our research group also found [18] that AT1-AAs could contract capacity blood vessels (thoracic aorta) and resistance blood vessels (coronary, middle cerebral artery) of rats. These studies suggested that AT1-AAs in patients may be closely related to vascular activities.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…It has been demonstrated that AT1-AAs increased the expression of tissue factor [24] , induced Ca 2+ release [25] and activated NADPH oxidase [10] in VSMCs [9] . Our research group also found [18] that AT1-AAs could contract capacity blood vessels (thoracic aorta) and resistance blood vessels (coronary, middle cerebral artery) of rats. These studies suggested that AT1-AAs in patients may be closely related to vascular activities.…”
Section: Discussionsupporting
confidence: 61%
“…So the increase of LDH is often viewed as one of the hallmarks of cell disintegration and necrosis. In order to reduce the interference caused by serum, total IgGs from AT1-Ab positive anti-sera of the immunized rats were purified according to previous studies [18] . Then the immunoglubulins were added to isolated cultured HUVECs, and LDH activity significantly increased after a certain time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Thereafter, studies both in vivo and in vitro showed that AT1AA have biological effects, including Ca 2+ release in vascular smooth muscle cells, NADPH (nicotinamide adenine dinucleotide phosphate) oxidase stimulation, nuclear factor-ÎșB, and JAK-STAT (Janus Kinase and Signal Transducer and Activator of Transcription pathway) activation, and induction of a preeclamptic-like syndrome in pregnant mice. [19][20][21][22][23][24] Circulating autoantibodies against the AT1 were detected in one third of patients with malignant hypertension secondary to renovascular disease, 10 and also in patients with acute renal transplant rejection and malignant hypertension. 12 Altogether these findings suggested that they could be a marker for vascular damage, rather than high BP per se.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our present data do not directly demonstrate an agonistic activity of AT1AA on AT1 receptors; however, previous studies indicated that increased levels of AT1AAs, as detected by this ELISA assay, cause vascular constriction and other biological effects that are held to occur through activation of AT1 receptor. 21,24 The following strengths are, however, also to be noted: this study was carried out according to the STARD Committee recommendations, 40 in that strict diagnostic criteria based on adrenal vein sampling, pathology, and follow-up information were used for diagnosing APA; moreover, different positive and negative control populations were recruited, and a stateof-the-art statistical analysis was exploited to assess diagnostic accuracy and compare different tests.…”
Section: Limitations and Strengthsmentioning
confidence: 99%